Environmental Managmenet Accounting – Priorities to the Reporting Company Systems - ANDREEA PAULA DUMITRU (Global Economic Observer)
Environmental management accounting serves as a mechanism for identifying and measuring the full spectrum of environmental costs of current production processes and the economic benefits of pollution prevention or cleaner processes, and to integrate these costs and benefits into day-to-day business decisionmaking. For the last decade, corporate environmental accounting has gained increased importance in practice, of which cost accounting receives most attention. Limits of traditional financial and cost accounting methods to reflect efforts of organizations towards sustainability and to provide management with information needed to make sustainable business decisions have been broadly recognized. Information on environmental performance of organizations might be available to some extent, but, decision-makers of internal company, as well as those in public authorities, are seldom able to link environmental information to economic variables and are crucially lacking environmental cost information. As a consequence, decision makers fail to recognize the economic value of natural resources as assets, and the business and financial value of good environmental performance. Beyond “goodwill” initiatives, a few market-based incentives exist to integrate environmental concerns in decision-making. This paper gives an overview of the approaches of environmental management accounting and we analyze environmental cost in condition by current economic context.